Tense, Aspect and Aktionsart in Classical Latin: Towards a New Approach. Issue 1 (1st January 2018) - Aerts, Simon
Abstract : This paper introduces the framework for a new project on the categories of tense, aspect and Aktionsart in Latin. In the first section, the relevant concepts are defined in terms of general linguistics. The second section provides an overview of the existing theories regarding the verb system and the categories of tense and aspect in Latin. Their shortcomings are listed while the strong points serve as the basis for the development of the current framework. In the third section, Bache's [2008. English Tense and Aspect in Halliday's Systemic Functional Grammar: A Critical Appraisal and an Alternative . Discussions in Functional Approaches to Language. London: Equinox.] SFL-inspired account of English tense and aspect is applied to the Latin verb system, conceptualizing tense and aspect in terms of three metafunctions or dimensions of meaning: ideational (representation of reality), textual (presentation of the text) and interpersonal (interaction with the audience). In the fourth section, the framework is illustrated with texts from Caesar, Livy and Sallust, showing that "perspective" (focalization) is essential to the linguistic analysis of narratives.